Electronic structural critique of interesting thermal and optical properties of C17Ge germagraphene. Issue 16 (7th April 2020) - Datta, Sujoy; Jana, Debnarayan
Abstract : We report a theoretical attempt to understand the involvement of the electronic structure in producing spin Hall conductivity and in determining the optical and thermal properties of germagraphene, a buckled two-dimensional material with low work function. Abstract : In this communication, we report a theoretical attempt to understand the involvement of the electronic structure in determining the optical and thermal properties of C17 Ge germagraphene, a buckled two-dimensional material. The structure is found to be a direct bandgap semiconductor with low carrier effective mass. Our study has revealed the effect of spin–orbit coupling on the band structure, and the appearance of spin Hall current on the material. The selectively high blue to ultraviolet light absorption, and a refractive index comparable to flint glass, open up the possible applicability of this material for optical devices. From an electronic structural point of view, we investigate the reason behind its moderately high Seebeck coefficient and power factor which are comparable to traditional thermoelectric materials. Besides its narrow bandgap and relatively smaller work function of 4.361 eV, compared to graphene (4.390 eV) and germanene (4.682 eV), ensures easier removal of electrons from the surface. This material turns out to be an excellent alternative for future semiconductor applications, from optical to thermal devices.